THE EFFECT OF RECTAL PROGESTERONE ON DOPPLER PARAMETERS OF THE UTERINE ARTERIES FOR THE PREVENTION OF PRETERM DELIVERY IN IRAQI POPULATION - Farhan, Fatin Shallal; Hameed, Ban Hadi; Zghair, Muna Abdulghani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The effectiveness of progesterone in the prevention of threatened preterm labor has been established for many years, but the preferable route, dose, and duration of treatment are until now under the evaluation of researches. The aim of this study was to determine the effect of rectal progesterone on Doppler indices of the uterine arteries in pregnant women with threatened preterm delivery. Methods: A prospective case–control study was conducted at the obstetric ward and the Outpatients Department of Al-Yarmouk Teaching Hospital in Baghdad for the period of 1 year from April 1, 2017, to April 1, 2018. 100 women were enrolled in the study, 50 of them were pregnant women with a diagnosis of preterm labor assigned as a study group and the other 50 were apparently healthy pregnant women of the same gestational age assigned as a control group. Doppler study of uterine arteries was done to all participants, and the results were compared for both groups. The patients with preterm labor received nifedipine tocolysis initially until contractions subsided and Doppler study had been repeated for those women after 1 week of rectal progesterone therapy. Results: The study group had a significantly higher resistance index (RI) than the control group (0.58 vs. 0.52) as p<0.05, in spite of the pulsatility index (PI) being higher for the study group compared to the control group (0.78 vs. 0.77) but this difference was not statistically significant. The RI before the therapy (0.58) was significantly higher than the index after therapy (0.52), and the PI was again significantly higher before therapy (0.78) than after therapy (0.71) as p<0.05. During the follow-up period, 3 (6.5%), 4 (8.7), and 39 (84.8%) patients delivered within 1 week, after 1 week, and at term, respectively. Conclusion: Rectal progesterone can arrest threatened preterm labor, and this effect is possible in part explained by its action on uterine arteries.